GO DIGITAL BATIK 786 DESA KOLELET WETAN-RANGKASBITUNG SEBAGAI UPAYA PERLUASAN PASAR DENGAN DIGITAL MARKETING - Fitrianti, Rizqi; Susilawati, Eka; Endayani, Endayani; Laelasari, Anggrum; Fadilah, Aulia Dea (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Batik is one of the archipelago’s treasures that is increasingly being marketed optimally. Batik 786 ‘Batikna Urang Banten’, one of the MSMEs in Kolelet Wetan Village, Rangkasbitung, Banten, has been in existence for five years but has not yet been touched by digitalization. As a result, its marketing is still done in a conventional manner. The production site is also not easily accessible to a wider market, so Batik 786 needs additional efforts to boost its sales and brand recognition. This initiative aims to expand Batik 786’s target market through digital marketing by creating an account on one of Indonesia’s e-commerce platforms, Shopee. The initiative is carried out in the form of training sessions with four meetings. From an introduction to e-commerce to a simulation of the checkout process until the product reaches the consumer. The materials provided by the Student Work Study Program (KKM) Group 56 of Bina Bangsa University have helped Batik 786 become digitally literate and ready to compete in the national market. The results of this community service initiative demonstrate an increase in Batik 786’s capacity in digital marketing. The owner of Batik 786 can now easily expand their marketing efforts optimally through digital marketing.